School Management System / Peterson @ Robinson J. Samuel - J. Samuel, Peterson @ Robinson (2003)
The School Management System (ScMS) is an electronic solution to the current manual file system that is practiced in most of the Malaysian schools. ScMS is a web-based information system that enables school administrators in particular principals, senior assistants and teachers to manage resources, processes and coordinate routine school activities. It helps to cut down on bureaucratic red tape and enables the transfer of data at much faster rate. In the outdated manual file system, there is no central repository on student or staff particulars. Retrieving data from the manual files is both tedious and cumbersome. Developing a computerized information system helps to reduce teachers workload by automating most of the routine processes. The School Management System can speed-up retrieval of study data, staff data, summarize attendance and analyze students result. It can even generate absentee report. In a nutshell, the ScMS when fully utilized would no only be a time saving efficient system but also improve productivity and bring about far-reaching benefits to the overall administration would facilitate more effective teaching and learning.